The Role of Amputation and Myoelectric Prosthetic Fitting in Patients with Traumatic Brachial Plexus Injuries. (17th August 2022) - Cantwell, Sean R.; Nelson, Andrew W.; Sampson, Brandon P.; Spinner, Robert J.; Bishop, Allen T.; Pulos, Nicholas; Shin, Alexander Y.
Abstract : Background: A cohort of patients with traumatic brachial plexus injuries (BPIs) underwent elective amputation following unsuccessful surgical reconstruction or delayed presentation. The results of amputation with and without a myoelectric prosthesis (MEP) using nonintuitive controls were compared. We sought to determine the benefits of amputation, and whether fitting with an MEP was feasible and functional. Methods: We conducted a retrospective review of patients with BPI who underwent elective upper-extremity amputation at a single institution. Medical records were reviewed for demographics, injury and reconstruction details, amputation characteristics, outcomes, and complications. Prosthesis use and MEP function were assessed. The minimum follow-up for clinical outcomes was 12 months. Results: Thirty-two patients with BPI and an average follow-up of 53 months underwent elective amputation between June 2000 and June 2020. Among the cases were 18 transhumeral amputations, 12 transradial amputations, and 2 wrist disarticulations. There were 29 pan-plexus injuries, 1 partial C5-sparing pan-plexus injury, 1 lower-trunk with lateral cord injury, and 1 lower-trunk injury. Amputation occurred, on average, at 48.9 months following BPI and 36.5 months following final reconstruction. Ten patients were fitted for an MEP with electromyographic signal control from muscles not normally associated with the intended function (nonintuitive control). Average visual analog scale pain scores decreased post-amputation: from 4.8 pre-amputation to 3.3 for the MEP group and from 5.4 to 4.4 for the non-MEP group. Average scores on the Disabilities of the Arm, Shoulder and Hand questionnaire decreased post-amputation, but not significantly: from 35 to 30 for the MEP group and from 43 to 40 for the non-MEP group. Patients were more likely to be employed following amputation than they were before amputation. No patient expressed regret about undergoing amputation. All patients in the MEP group reported regular use of their prosthesis compared with 29% of patients with a traditional prosthesis. All patients in the MEP group demonstrated functional terminal grasp/release that they considered useful. Conclusions: Amputation is an effective treatment for select patients with BPI for whom surgical reconstruction is unsuccessful. Patients who underwent amputation reported decreased mechanical pain, increased employment rates, and a high rate of satisfaction following surgery. In amputees with sufficient nonintuitive electromyographic signals, MEPs allow for terminal grasp/release and are associated with high rates of prosthesis use. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.